ISLAM DAN KONSEP PENGEMBANGAN KELEMBAGAAN BERBASIS MULTIKULTURAL - Zainuddin (Qolamuna : Jurnal Studi Islam, 2026)
Islam, as a universal religion, embodies fundamental values ​​that emphasize justice, equality, tolerance, and respect for diversity. These values ​​serve as an important foundation for institutional development amidst the reality of a multicultural society. This article aims to analyze the concept of multicultural-based institutional development from an Islamic perspective and its relevance in building inclusive and equitable institutions. The research method used is a literature study by examining classical and contemporary Islamic sources, as well as literature related to multiculturalism and institutional development. The results of the study indicate that Islam normatively and historically supports institutional management that respects cultural, ethnic, and religious differences, and encourages the creation of social harmony and cohesion. The concept of multicultural-based institutional development in Islam is not only theoretical but also applicable in addressing the social challenges of a pluralistic society. Therefore, the integration of Islamic values ​​and the principles of multiculturalism can be a strategic approach to strengthening adaptive and sustainable institutions. Keywords : Islam, Institutional Development, Multiculturalism, Islamic Values, Plural Society